Regulating Online Broadcast Media in Malaysia: Legal Study of Compliance and Regulatory Enforcement in Relation to Hate Speech and Offensive Materials - Islam, Zahidul; Mokhtar, Khairil Azmin Bin; Afandi, Nor Hafizah Bt Mohd Badrol; Shafy, Mohamed Affan (International Journal of Psychosocial Rehabilitation, 2020)
Online Broadcasting services are increasing dramatically without any proper regulatory framework and affecting local traditional broadcaster. Nowadays, online broadcasting services are popular to the customer for online movie sites like Netflix, Iflix Pandora, Amazon Prime Video, Hotstar, Hulu. These types of online video sites broadcasting original video content without any censorship which makes film censorship board useless. This purpose of this study was to analyse the effectiveness and enforceability of the Malaysian Communications and Multimedia Act (1998) on complying online media broadcast services to the laws and regulations of the country. The paper analyses the two major online media broadcast services in the country and looks in to their terms and conditions of service agreement between their customers and the controversial content made available through their services. The paper also identifies the inadequacies of legal action by the legally mandated enforcement agency, the Malaysian Communications and Multimedia Commission (MCMC). This study will use a legal and doctrinal research methodology. Data collection will be based on content analysis from the primary and secondary legal sources. This study found that the content provided by the service providers did not comply with the laws and regulations of Malaysia and in some instance they were not only uncompliant but have designed their service agreements with their customers in a manner to avoid legal responsibility for the nature of the content they provided.